Twenty-One Reasons for Implementing the Act-Belong-Commit—‘ABCs of Mental Health’ Campaign - Robert J. Donovan (MDPI AG, 2021)
While there has been increased attention worldwide on mental health promotion over the past two decades, what is lacking in many countries around the globe is practical knowledge of what constitutes a population-wide mental health promotion campaign, and how such a campaign can be implemented. This paper provides such knowledge based on the development, implementation and evaluation of the Act-Belong-Commit campaign, the world’s first comprehensive population-wide public mental health promotion campaign which was launched in 2008 in Western Australia. Given the learnings from the full-scale implementation and evaluation of the campaign in Western Australia and its expansion nationally and internationally, along with the continuing and expanding evidence base for the campaign constructs, we crystallise 21 reasons why jurisdictions who wish to achieve the goals of the WHO and adopt the recommendations of the European framework on mental health and wellbeing should consider adopting or adapting Act-Belong-Commit when considering implementing a public mental health promotion campaign.